Catalase and Carbonic Anhydrase Enzyme Activities, and Some Mineral-Heavy Metal Concentrations in Newborns with Congenital Malformations - MERAL, İSMAİL; Melek, Mehmet; Demir, Halit; Kirimi, Ercan; Meral, Ismail; Keskin, Sıddık (My University, 2011)
Objective: The aim of this study is to evaluate the factors such as antioxidant condition and mineral-heavy metal level association that may play a role in development of congenital malformations. Material and Methods: Fifteen healthy neonates as control group and 15 neonates with various congenital malformations were included study. Erythrocyte cataly (CAT) which is an antioxidant enzyme, erythrocyte carbonic anydrase (CA) enzyme activities which play a important role in acid-base balance, serum copper (Cu), lead (Pb), zinc (Zn), cadmium (Cd), iron (Fe), manganese (Mn) and magnesium (Mg) were measured from venous blood samples of each subject. Results: Erythrocyte CAT enzyme activity, serum Zn and Fe levels were statistically significantly decreased (P<0.05) in the study group while serum Cu and Cd levels were statistically significantly high (P<0.05)in the study group when compared to the control group. A negative correlation between erythrocyte CA activity and serum Pb levels was found in the study group. In the control group, negative correlations were found between erythrocyte CAT activity and serum Pb levels; serum Mg and Cu levels; and serum Cd and Mn levels. In addition, in the control group a positive correlation between serum Zn and Cu levels; erythrocyte CA activity and serum Mn levels was found. Conclusion: Our results suggest that erythrocyte CAT enzyme activity and serum Cu, Zn, Fe and Cd levels may play a role in pathogenesis of congenital malformations. The oxidative stress that rise as a result of an imbalance between prooxidant and antioxidant reactions seems to be associated with congenital malformations. Further studies are needed to confirm the association of antioxidant condition and mineral-heavy metal levels in the pathogenesis of congenital malformations.